Urban Green Space Regulation: Challenges to Water Resources Conservation in Indonesia and Australia - Jundiani, Jundiani; Fadli, Moh.; Qurbani, Indah Dwi; Kurniaty, Rika; Hulwanullah, Hikam (Journal of Human Rights, Culture and Legal System, 2024)
The escalating environmental crisis and pressing water resource conservation issues globally necessitate comprehensive research. This study investigates urban green space regulations and water resource conservation challenges in Indonesia and Australia. Employing a comparative analysis, it examines the legal frameworks, policies, and implementations in both countries. The research aims to identify innovative and sustainable strategies for water resource protection. Findings reveal substantial disparities in regulatory approaches, public involvement, and the integration of green technologies in green space management between the two nations. Indonesia needs help enhancing institutional capacity and integrating green space policies into urban planning, while Australia focuses on climate change adaptation and sustainable water resource management. The study advocates cross-sectoral collaboration and ecosystem principles in green space regulations for practical water conservation objectives. It contributes fresh perspectives on legal and policy frameworks for addressing water resource conservation challenges through urban green space management, offering recommendations for cohesive and sustainable policy development.